Environmental and behavioural head and neck cancer risk factors - Vučičević Boras, Vanja; Fučić, Aleksandra; Baranović, Sandra; Blivajs, Igor; Milenović, Maja; Bišof, Vesna; Rakušić, Zoran; Ceppi, Marcello; Bruzzone, Marco (Central European journal of public health, 2019)
OBJECTIVES: The high incidence of head and neck cancer (HNC), significantly associated with living environment and behaviour, can be prevented more efficiently. The aim of this study was to evaluate the environmental and behavioural risk factors for HNC. METHODS: Using a detailed questionnaire on social status, education, living and occupational environment exposures, family cancer and lifestyle, HNC patients (103 cases, 76.7% of men) were compared with control subjects (244 subjects, 73% of men) balanced by age: mean (standard deviation) 63.8 (9.3) and 63.8 (9.0) for cases and controls, respectively. RESULTS: The results of this study showed that smoking and low education were significant risk factors for HNC regardless of sex. Family HNC and breast cancer were significant predictors of HNC risk. CONCLUSION: The study confirmed previous results that smoking and low education are significantly associated with HNC. Additionally, results pointed to significant HNC and breast cancer risk in HNC patient's families that may have originated from passive smoking or a smoking habit stemming from social environments that support it. Better dissemination programmes regarding smoking risks for children and adults are needed, targeting not only individuals but also families.
Keywords: family cancer; Genetic Predisposition to Disease; head and neck cancer; nádory hlavy a krku; kouření; Male; zdravé chování; Incidence; sexuální faktory; průzkumy a dotazníky; mužské pohlaví; Head and Neck Neoplasms; studie případů a kontrol; incidence; education; Adult; sociální determinanty zdraví; smoking; dítě; Child; Social Determinants of Health; věkové faktory; aetiology; Smoking; ženské pohlaví; znečištění tabákovým kouřem; Health Behavior; Humans; Tobacco Smoke Pollution; Sex Factors; Surveys and Questionnaires; rizikové faktory; Alcohol Drinking; pití alkoholu; Age Factors; dospělí; genetická predispozice k nemoci; Female; Risk Factors; lidé; Case-Control Studies